Human capital vs. social capital: Influences on egg productivity in southern Ethiopia - Innes, G. (University of San Francisco, 2010)
This study explores the relationships extension services, formal education and social networks have with egg production in Southern Ethiopia. A cross section survey of 112 farming households was collected and, using a semi-log linear production model, a detailed analysis was undertaken to evaluate these relationships. The data suggests social membership has a positive and significant influence on egg production but no discernable association was found between production and extension services. A weak, biased and unsupportive extension service was offered as a possible explanation. Possessing some primary education was also observed to have a positive and significant association with egg yields. Furthermore, the interaction between social members with different levels of education suggests that increasing levels of education have an increasing partial effect on the influence social capital has on egg production. This concurs with theory. Conclusions are that social capital and primary education are important to the productivity of female egg producers in Southern Ethiopia, but extension services are not.